Cytokines, Hormones and Cellular Regulatory Mechanisms Favoring Successful Reproduction - Piccinni, Marie-Pierre; Raghupathy, Raj; Saito, Shigeru; Szekeres-Bartho, Julia (Frontiers in Immunology, 2021)
Its semi-allogeneic nature renders the conceptus vulnerable to attack by the maternal immune system. Several protective mechanisms operate during gestation to correct the harmful effects of anti-foetal immunity. Progesterone is indispensable for pregnancy, and it affects immune functions directly or via mediators. The progesterone-induced mediator - PIBF - acts in favour of Th2-type immunity, by increasing the production of Th2 cytokines. Except for implantation and parturition, pregnancy is characterized by a Th2-dominant cytokine pattern. Progesterone and the orally-administered progestogen dydrogesterone upregulate the production of Th2-type cytokines and suppress the production of Th1 and Th17 cytokine production in vitro. The Th1-type cytokines TNF-α and IFN-γ and the Th17 cytokine IL-17 have embryotoxic and anti-trophoblast activities. These cytokine-modulating effects and the PIBF-inducing capacity of dydrogesterone may contribute to the beneficial effects of dydrogesterone in recurrent spontaneous miscarriage and threatened miscarriage. IL-17 and IL-22 produced by T helper cells are involved in allograft rejection, and could be responsible for the rejection of paternal HLA-C-expressing trophoblast. Th17 cells and Th22 cells produce IL-22 and IL-17 in association with Th2- or with Th1-type cytokines. Due to their plasticity IL-17 and IL-22 producing Th cells are not harmful if they also produce IL-4. Another protective mechanism is connected with the expansion and action of regulatory T cells, which play a major role in the induction of tolerance both in pregnancy and in cancer patients. Clonally-expanded Treg cells increase at the foeto-maternal interface and in tumour-infiltrating regions. While in cancer patients, clonally-expanded Treg cells are present in peripheral blood, they are scarce in the peripheral blood of pregnant women, suggesting that foetal antigen-specific tolerance is restricted to the foeto-maternal interface. The significance of Treg cells in maintaining a normal materno-foetal interaction is underlined by the fact that miscarriage is characterized by a decreased number of total effector Treg cells, and the number of clonally-expanded effector Treg cells is markedly reduced in preeclampsia. We present an overview of these mechanisms show how they operate during gestation, and how their failure might lead to pregnancy pathologies.